Hepatoprotective Effect of Sodium Molybdate on Carbon Tetrachloride-induced Liver Damage in Rats - Haeri Rohani A (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2011)
Background and Objectives: The liver as a key organ of metabolism and excretion is constantly endowed with the task of detoxification. Hepatotoxicants can induce various disorders of the organ. Carbon tetrachloride (CCl4) is a potent hepatotoxin producing centrilobular hepatic necrosis and is widely used for animal models of hepatotoxicity. Molybdenum functions as a co-factor for a limited number of enzymes including xanthine oxidase, aldehyde oxidase and sulfite oxidase in mammals, and is believed to be an essential trace element in human and nutrition. The aim of the present study was to evaluate the protective effect of sodium molybdate against experimentally induced-CCl4 liver injury.Methods: Adult male rats were orally administered with different doses of sodium molybdate (0.05, 0.1 and 0.2g/kg bw/daily) along with CCl4 (50% CCl4, in olive oil, 1ml/kg bw, intrapertioneally) twice a week for 28 consecutive days. Biochemical parameters like alanine amino transferase, aspartate amino transferase, alkaline phosphatase and total protein levels in the serum were determined. Results: In present study, the level of serum markers such as alanine amino transferase, aspartate amino transferase, and alkaline phosphatase were significantly increased in CCl4 treated rats. While Simultaneous treatment of sodium molybdate at doses 0.05, 0.1 and 0.2g/kg bw significantly decreased alanine amino transferase, aspartate amino transferase and alkaline phosphatase at the dependent dosage manner. Moreover, it had no effect on serum total protein levels. Conclusion: The results of this study demonstrate the hepatoprotective effect of molybdenum and thus scientifically supports the use of this trace element for treatment of liver disorders.